Dificuldade para dormir em idosos: influência da depressão e estresse - Iroldi, Grazielle Ferreira (Universidade Federal de São Carlos, 2020)
As the population ages, it presents a different epidemiological profile with a progressive increase in the prevalence of non-transmissible diseases and chronic diseases (NCDs). The Pan American Health Organization highlighted stress and depression among NCDs that commonly affect the elderly. In addition, aging-related changes and sleep disorders are often described. This study aimed to identify an association between emotional variables (stress and depression) and the self-report of difficulty sleeping in the elderly. It was a descriptive, quantitative and cross-sectional study in which 341 elderly people registered in Family Health Units in the city of São Carlos - SP were interviewed, divided into two groups: (a) Self-reported group without difficulty and (b) Group with difficulty sleeping self-reported. The instruments for data collection were: Characterization Sheet for the Elderly with Specific Question of Difficulty in Self-Reported Sleep, Perceived Stress Scale and Geriatric Depression Scale. The data obtained were entered into a bank in the program Statistical Package for Social Sciences (SPSS) for Windows to perform descriptive and comparative statistical analyzes. All stages of this work followed the ethical guidelines for research involving human beings. The elderly were mostly female (76.8%), married or with partners (90.3%), with an average age of 69.6 years, low education (M = 3.81 years of age). education) and income (M = R $ 2,302.21). The difficulty to sleep was self-reported in 47.5% of the sample (n = 162). The stress levels of the elderly group with difficulty sleeping were higher (M = 21.29 points) than in the group without difficulty sleeping (M = 15.97) (U = 10034.50; p = 0.010). In addition, elderly people with difficulty sleeping had higher scores on the scale of depressive symptoms (M = 4.41 points) when compared to those without difficulty sleeping (M = 3.09 points) (U = 10427.50, p = 0.000). Given the proposed objective, it can be concluded that there is an association between emotional variables and difficulty sleeping in the elderly.
Difficulty sleeping in the elderly: influence of depression and stress
Keywords: Sono; Estresse Psicológico; Depressão; Idoso; Sleep; Stress, Psychological; Depression; Elderly; CIENCIAS DA SAUDE